2014
DOI: 10.1007/s11165-014-9438-6
|View full text |Cite
|
Sign up to set email alerts
|

Global Patterns in Students’ Views of Science and Interest in Science

Abstract: International studies have shown that interest in science and technology among primary and secondary school students in Western European countries is low and seems to be decreasing. In many countries outside Europe, and especially in developing countries, interest in science and technology remains strong. As part of the large-scale European Union funded 'Science Education for Diversity' project, a questionnaire probing potential reasons for this difference was completed by students in the UK, Netherlands, Turk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
311
2
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 575 publications
(388 citation statements)
references
References 23 publications
11
311
2
12
Order By: Relevance
“…Some papers also offered indications of alpha having a threshold or cut-off as an acceptable, sufficient or satisfactory level. This was normally seen as ≥0.70 (five instances) or >0.70 (three instances) although one article more vaguely referred to "the acceptable values of 0.7 or 0.6" (Griethuijsen et al, 2014).…”
Section: Characterising Values Of Cronbach's Alphamentioning
confidence: 99%
See 2 more Smart Citations
“…Some papers also offered indications of alpha having a threshold or cut-off as an acceptable, sufficient or satisfactory level. This was normally seen as ≥0.70 (five instances) or >0.70 (three instances) although one article more vaguely referred to "the acceptable values of 0.7 or 0.6" (Griethuijsen et al, 2014).…”
Section: Characterising Values Of Cronbach's Alphamentioning
confidence: 99%
“…Griethuijsen et al (2014) reported a cross-national study looking at student interests in science where "several of the values calculated for Cronbach's alpha are below the acceptable values of 0.7 or 0.6" (p.588). For example, an "interest in school science" factor was based on a subset of five questionnaire items with Cronbach's alpha of 0.502 (p.589), and the "interest in domestic activities" factor was based on a subset of three items with alpha of 0.446 (p.590).…”
Section: Characterising Values Of Cronbach's Alphamentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, science education faces a great challenge. Recent international studies have shown that engagement with school science and motivation to choose science related career among secondary school students are alarming, as students actively reject science related career as a future career option (Kudenko & Gras-Velázquez, 2016;McFarlane, 2013;Van Griethuijsen et al, 2015). According to Gilbert and Justi (2016) evidence of students' lack of engagement in science classes is used to support widespread dissatisfaction regarding students' levels of attainment in international studies and with their disinclination to continue to study science related discipline in higher education institutions.…”
Section: Introductionmentioning
confidence: 99%
“…According to Gilbert and Justi (2016) evidence of students' lack of engagement in science classes is used to support widespread dissatisfaction regarding students' levels of attainment in international studies and with their disinclination to continue to study science related discipline in higher education institutions. This has led to concern among policymakers about their nation's science and technology workforce, as well as the scientific literacy of their populations (Van Griethuijsen et al, 2015). In regard to international studies, for example, the Trends in International Mathematics and Science Study (TIMSS) has shown disturbing trends among many developing countries.…”
Section: Introductionmentioning
confidence: 99%